(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe clinical and paraclinical characteristics of epilepsy in children. Subjects and methods: A descriptive cross-sectional study of 112 epileptic children at Nghe An Obstetrics and Pediatrics Hospital from January 2022 to December 2022. Results: The average age of pediatric patients was 51.9 months, male children accounted for 59.8%. The most common age of disease onset is under 24 months (48.2%). Generalized epilepsy accounts for the highest rate (59.8%), followed by partial epilepsy (38.4%), with only 2.7% having unclassified epilepsy. In generalized epilepsy, tonic-clonic seizures account for 51.5%, West syndrome accounts for 15.2%. In focal epilepsy, there are mainly simple partial seizures (81.4%), followed by complex partial seizures (16.3%). There were 30 patients who had the Raven test and 72 patients who had the Denver II test, identifying 46.1% of patients with mainly mild and moderate developmental delay (37.3%). The rate of abnormal electroencephalogram was 69.6%; brain damage on magnetic resonance is 30.4%, of which structural brain damage accounts for 10.7%. Conclusion: Childhood epilepsy often begins in the first years of life, when a high rate of generalized epilepsy is diagnosed (59.8%), often accompanied by psycho-motor retardation. Interictal electroencephalogram had 69.6% abnormality; 30.4% saw lesions on magnetic resonance imaging.